Influence of specimen orientation on fatigue crack growth in 7050-T7451 and 2050-T8 aluminium alloys. (November 2022) - Jesus, J.S.; Antunes, F.V.; Prates, P.; Branco, R.; Antunes, P.V.; Borrego, L.P.; Neto, D.M.
Highlights: Lower FCGR rates are obtained in the L-T orientation. Crack deflection induces: crack closure, longer crack path and lower effective ΔK. Larger cyclic plastic zone in L-T direction leads to higher crack closure level. Abstract: The effect of L-T and S-T orientations on FCGR is here in studied in 7050-T7451 and 2050-T8 aluminum alloys. The Low-cycle fatigue tests and hardness measurements have shown that specimen orientation has a minor effect on material plastic hardening. Lower FCG rates are obtained for both materials in the L-T orientation, which can be associated to the resistance at grain boundaries. The larger cyclic plastic zone attained in the L-T direction leads to an increase of the plasticity inducing crack closure. Crack deflection observed for L-T direction also affects the FCGR due to roughness inducing crack closure, longer crack path and lower effective ΔK.